Net Equatorward Shift of the Jet Streams When the Contribution From Sea‐Ice Loss Is Constrained by Observed Eddy Feedback. Issue 23 (10th December 2022) - Screen, James A.; Eade, Rosemary; Smith, Doug M.; Thomson, Stephen; Yu, Hao
Abstract: We examine the midlatitude jet stream responses to projected Antarctic and Arctic sea‐ice loss and global ocean warming in coordinated multi‐model experiments from the Polar Amplification Model Intercomparison Project. Antarctic and Arctic sea‐ice loss cause an equatorward shift of the winter jet stream in the southern and northern hemisphere, respectively, on average across the models. Models with stronger eddy feedback simulate farther equatorward jet shifts in response to both Antarctic and Arctic sea‐ice loss. The models simulate too weak eddy feedback compared to the real world, particularly in the northern hemisphere, resulting in an underestimation of the boreal jet response to Arctic sea‐ice loss. More precise estimates of the jet shifts are obtained by using the observed eddy feedback as a constraint and suggest that the equatorward jet shifts in response to Antarctic and Arctic sea‐ice loss exceed in magnitude the simulated poleward shifts due to ocean warming. Plain Language Summary: Winter weather in the midlatitudes of the northern and southern hemispheres is influenced by the position of the jet streams. In a warming climate, the jet streams may move from the current average location. Past work has suggested that sea‐ice loss and ocean warming affect the jet stream location in opposite directions, leading to a "tug‐of‐war" on the jet. It is unclear which factor "wins" this tug‐of‐war and so, in what direction the jet stream may shift in the future. We use new climate model experiments to better measure the separate effects of sea‐ice loss and ocean warming on the jet streams. Antarctic and Arctic sea‐ice loss cause an equatorward shift of the winter jet stream in the southern and northern hemisphere, respectively. Models tend to underestimate these jet shifts in response to sea‐ice loss compared to the real world. Ocean warming causes a poleward jet shift that approximately cancels out the equatorward shift due to sea‐ice loss, in both hemispheres. However, when we account for the model underestimation of the jet shifts in response to sea‐ice loss, we find that sea‐ice loss "wins" the tug‐of‐war, which suggests the jets move equatorward in a warmer climate. Key Points: Antarctic and Arctic sea‐ice loss cause an equatorward shift of the winter jet stream in the southern and northern hemisphere, respectively Models with stronger eddy feedback simulate farther jet shifts in response to both Antarctic and Arctic sea‐ice loss Observationally constrained equatorward jet shifts due to sea‐ice loss exceed in magnitude the simulated poleward shifts due to ocean warming